2007
DOI: 10.1088/0953-8984/20/03/035210
|View full text |Cite
|
Sign up to set email alerts
|

Structural and electronic properties of NM-doped ceria (NM = Pt, Rh): a first-principles study

Abstract: The effects of noble metal (NM) dopants (NM = Pt, Rh) on the structural and electronic properties of ceria are studied using a density functional theory (DFT) method, with the inclusion of on-site Coulomb interaction (DFT+U). It is found that these NM dopants give rise to large perturbations of the atomic and electronic structures of ceria and induce metal-induced gap states at the Fermi level suitable for accommodating extra electrons, thereby lowering the reduction energy of ceria and making the NM-doped cer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
50
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(58 citation statements)
references
References 57 publications
5
50
2
Order By: Relevance
“…These results would suggest that the removal of an oxygen next to the dopant during formation of a charge-compensating vacancy costs energy. 19,20 This is at variance with previous X-ray photoelectron spectroscopy studies that indicate Pd and Pt to be present preferentially in the +2 oxidation state, and accompanied by spontaneously formed charge-compensating vacancies. 9,18 Despite the reported improvements in catalytic activity and OSC, the underlying reason for these has remained unclear.…”
Section: Introductioncontrasting
confidence: 51%
See 4 more Smart Citations
“…These results would suggest that the removal of an oxygen next to the dopant during formation of a charge-compensating vacancy costs energy. 19,20 This is at variance with previous X-ray photoelectron spectroscopy studies that indicate Pd and Pt to be present preferentially in the +2 oxidation state, and accompanied by spontaneously formed charge-compensating vacancies. 9,18 Despite the reported improvements in catalytic activity and OSC, the underlying reason for these has remained unclear.…”
Section: Introductioncontrasting
confidence: 51%
“…Hermansson and co-workers have previously used the local density approximation (LDA)+U approach to model the doping of CeO 2 with Pd and Pt, 19,20 with the formation of the charge-compensating vacancy incorrectly considered as the reduction energy. The authors reported that the replacement of a Ce IV in both cases resulted in a very small relaxation around the dopants.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations